Management of progressive pulmonary nodules found during and outside of CT lung cancer screening studies - Meyer, Mathias; Henzler, Thomas; Bürgy, Daniel; Giordano, Frank Anton; Kostrzewa, Michael; Rathmann, Nils-Andreas; Pilz, Lothar R.; Manegold, Christian; Rößner, Eric (Journal of thoracic oncology, 2017)
Although the effectiveness of screening for lung cancer remains controversial, it is a fact that most lung cancers are diagnosed at an advanced stage outside of lung cancer screening programs. In 2013, the U.S. Preventive Services Task Force revised its lung cancer screening recommendation, now supporting lung cancer screening by low-dose computed tomography in patients at high risk. This is also endorsed by many major medical societies and advocacy group stakeholders, albeit with different eligibility criteria. In Europe, population-based lung cancer screening has so far not been recommended or implemented, as some important issues remain unresolved. Among them is the open question of how enlarging pulmonary nodules detected in lung cancer screening should be managed. This article comprises two parts: a review of the current lung cancer screening approaches and the potential therapeutic options for enlarging pulmonary nodules, followed by a meeting report including consensus statements of an interdisciplinary expert panel that discussed the potential of the different therapeutic options.